Feasibility of using Auto Mod‐MPI system, a novel technique for automated measurement of fetal modified myocardial performance index. (June 2014) - Lee, M.‐Y.; Won, H.‐S.; Jeon, E.‐J.; Yoon, H. C.; Choi, J. Y.; Hong, S. J.; Kim, M.‐J.
ABSTRACT Objectives To evaluate the reproducibility of measurement of the fetal left modified myocardial performance index (Mod‐MPI) determined using a novel automated system. Methods This was a prospective study of 116 ultrasound examinations from 110 normal singleton pregnancies at 12 + 1 to 37 + 1 weeks' gestation. Two experienced operators each measured the left Mod‐MPI twice manually and twice automatically using the Auto Mod‐MPI system. Intra‐ and interoperator reproducibility were assessed using intraclass correlation coefficients (ICCs) and the manual and automated measurements obtained by the more experienced operator were compared using Bland–Altman plots and ICCs. Results Both operators successfully measured the left Mod‐MPI in all cases using the Auto Mod‐MPI system. For both operators, intraoperator reproducibility was higher when performing automated measurements (ICC = 0.967 and 0.962 for Operators 1 and 2, respectively) than when performing manual measurements (ICC = 0.857 and 0.856 for Operators 1 and 2, respectively). Interoperator agreement was also better for automated than for manual measurements (ICC = 0.930 vs 0.723, respectively). There was good agreement between the automated and manual values measured by the more experienced operator. Conclusions The Auto Mod‐MPI system is a reliable technique for measuring fetal left Mod‐MPI and demonstrates excellent reproducibility. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.